2022
DOI: 10.1371/journal.pone.0275415
|View full text |Cite
|
Sign up to set email alerts
|

Association between physiotherapist burnout and working environment during the coronavirus disease 2019 pandemic in Japan: A multicenter observational study

Abstract: Burnout among physiotherapists has been reported worldwide during the coronavirus disease 2019 (COVID-19) pandemic. However, no information was found on the prevalence of burnout among physiotherapists in Japan during the COVID-19 pandemic. Physiotherapists directly providing physiotherapy to patients with COVID-19 in the red zone of 487 medical facilities were evaluated for the prevalence of burnout using the Japanese version of the Maslach Burnout Inventory-General Survey (MBI-GS). The association between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…In our previous study, we found that physiotherapists had an average sleep duration of 6 h during the COVID-19 pandemic [ 27 ], which was similar to the that for other HCPs [ 25 , 26 ], and that some physiotherapists had experienced decreased sleep duration and increased overtime hours. We hypothesized that working environment would be associated with sleep duration in physiotherapists as they provide physiotherapy and conduct daily work in an environment they had never experienced before the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 65%
“…In our previous study, we found that physiotherapists had an average sleep duration of 6 h during the COVID-19 pandemic [ 27 ], which was similar to the that for other HCPs [ 25 , 26 ], and that some physiotherapists had experienced decreased sleep duration and increased overtime hours. We hypothesized that working environment would be associated with sleep duration in physiotherapists as they provide physiotherapy and conduct daily work in an environment they had never experienced before the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 65%
“…A multicenter observational study was performed in Japan in physiotherapists (n=566) during the COVID-19 pandemic [35]. 17,5% of respondents hit the criteria for burnout (MBI-GS); furthermore, burnout syndrome was associated with a feeling of slight burden by infection control, the year of experience of physiotherapy, relaxation time, and staffing standards for physiotherapy that might be established in accordance with the number of beds [35]. Similar results were found out in another cross-sectional study among attending physicians (n=1061) of Japan that showed the prevalence (17,2%) of burnout syndrome (the MBI-GS) and its associated factors [36 p226].…”
Section: Asiamentioning
confidence: 99%
“…Istotnym problemem obnażonym przez pandemię były również niedobory kadrowe fizjoterapeutów [6,7], pogłębiające się za sprawą zaburzeń w systemie edukacji osób kształcących się w tym zawodzie, będących efektem trudności w organizacji zajęć praktycznych i klinicznych dla studentów fizjoterapii [8]. Kolejnym ograniczeniem zgłaszanym przez wielu fizjoterapeutów na świecie było pojawianie się w ich grupie wypalenia zawodowego oraz problemów psychologicznych w następstwie stresu oraz wysiłku związanego z pracą w warunkach pandemii [1,9].…”
unclassified
“…Inne badania z tego kraju wskazują, że w trakcie pandemii usługi rehabilitacyjne były wspierane narzędziami telezdrowia [1]. W Japonii w celu usprawnienia procedur rehabilitacyjnych wobec pacjentów w czasie trwania pandemii ustanowiono standardy kadrowe dla fizjoterapii wg liczby łóżek [9]. W Australii kładziono silny nacisk na przeciwdziałanie zaburzeniom pandemicznym w obszarze kształcenia praktycznego fizjoterapeutów, poprzez wdrażanie innowacyjnych rozwiązań w zakresie monitorowania procesów kształcenia oraz pozwalających na dynamiczne reagowanie na zmiany w systemie edukacji [8].…”
unclassified
See 1 more Smart Citation